Rapid and green synthesis of silver nanoparticles via sodium alginate media - Balavandy, Sepideh Keshan; Shameli, Kamyar; Zainal Abidin, Zurina (Electrochemical Science Group, 2015)
This study focuses on influence of accelerator in rapidly and green synthesis of silver nanoparticles (Ag-NPs) with the natural polymeric matrix. Silver nitrate, sodium alginate (Na-Alg) and sodium hydroxide have been used as silver precursor, stabilizer/reducing agent, and accelerator reagent, respectively. The resulting products have been confirmed to be Ag-NPs smaller than 20 nm using powder X-ray diffraction (PXRD), UV-visible spectroscopy (UV-vis), Fourier transform infrared (FT-IR) spectroscopy as well as transmission electron microscopy (TEM) and scanning electron microscopy. The colloidal solutions of Ag-NPs obtained at different volumes of NaOH show strong and different surface plasmon resonance (SPR) peaks, which can be explained from the TEM images of Ag-NPs and their particle size distribution. Compared with other synthetic methods, this work is rapid, green and simple to use. The newly prepared Ag-NPs may have many potential applications in chemical pharmaceutical and food industries.